2023
DOI: 10.1039/d2ta07792b
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal dichalcogenide micromotors with programmable photophoretic swarming motion

Abstract: Herein we report the light-triggered photophoretic motion of WS2 micromotors. The micromotors are prepared by liquid-phase exfoliation of pristine WS2 in water, resulting in a layered material with high photoconversion...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…35,36 Further details on the propulsion mechanism of photophoretic TMD-based microflakes can be found in the literature with insights into the swarming capabilities of such microflakes and an in-depth study of the interactions between micromotors and the surrounding media. 29 In addition, the holes and vacancies generated in the microflakes are active sites for the reaction with the solvent. Due to the reaction with free electrons and holes, ROS are generated.…”
Section: Paper Nanoscalementioning
confidence: 99%
See 1 more Smart Citation
“…35,36 Further details on the propulsion mechanism of photophoretic TMD-based microflakes can be found in the literature with insights into the swarming capabilities of such microflakes and an in-depth study of the interactions between micromotors and the surrounding media. 29 In addition, the holes and vacancies generated in the microflakes are active sites for the reaction with the solvent. Due to the reaction with free electrons and holes, ROS are generated.…”
Section: Paper Nanoscalementioning
confidence: 99%
“…The micromotors can move upon VIS light irradiation, reaching a speed of 6000 μm s −1 , along with ROS generation. 29 Given the photoconversion abilities of TMDs materials, along with their inherent antibacterial abilities, TMD-based photophoretic microflakes will be explored as an antimicrobial platform. Specifically, we describe the synthesis of photophoretic MoS 2 and WS 2 microflakes with inherent antibacterial activities for the inactivation of E. coli and S. aureus biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to TiO 2 , light-induced swarming behavior was observed in various types of semiconductors, for example organic photoactive molecules 24 and polymers, 25 silver chloride, 26 silver phosphate, 27 iron oxide, 28 or chalcogenide semiconductors. 29,30 The latter is also known for good thermodynamic stability, facile synthesizability and dopability, and unique optoelectrical properties that enable their application in solar cells, thin film transistors, diodes, or water splitting photoelectrocatalysts. 31 Recently, chalcogenide semiconductors have been applied as suitable materials for the fabrication of light-driven microrobots; X. Zhan et al 32 reported on preparation of Sb 2 Se 3 -based microrobots of anisotropic crystal structure that were navigated under polarized light.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, metal dichalcogenides, such as WS 2 and MoS 2 , were applied for the fabrication of photophoretic swarming microrobots. 29,30…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation